PENERAPAN GOOD GOVERNANCE TERHADAP PELAYANAN BEA PEROLEHAN HAK ATAS TANAH DAN BANGUNAN DI BADAN PENDAPATAN DAERAH KABUPATEN KUTAI TIMUR - Aswin Tri Astaman dan Maskan AF (DEDIKASI : Jurnal Ilmiah Sosial, Hukum, Budaya, 2020)
This study intend to determine the extent of the application of the principles of good governance and also know what are the obstacles in the process of applying these principles. This study was implemented in the revenue agency of the East Kutai Regency.To support the study, a sample of ten people was taken, five people are office employees and five people are taxpayer. The method used in this study is the interview method, then the type of research is descriptive qualitative.            Based on the results of study with a focus on rule of law, transparent, responsive, equity and accountability, conclusions can be drawn. Law enforcement has been implemented quite well and has been carried out accordingly. Services provided by the revenue agency have been carried out directly and openly to the public, The officers in providing services are good enough, it can be seen from the attitude of the officers are quite friendly, helping to complete the lack of copies of community files and other things in providing services, the ongoing service does not differentiate the management of files, all files are processed according to the type of files obtained, and The Office is always responsible for all types of file acquisition in the event of payment errors such as underpayment or overpayment of taxes.           As for the constraints, in accordance with the focus of study there are often misunderstandings of the public regarding applicable regulations, sometimes the officer is not in place when the service is in progress, lack of information regarding the period of completion of the files obtained, and a matter of time if there is an overpayment of tax refunds.